INSTAGRAM SEBAGAI MEDIA PEMASARAN PASCA COVID-19 DALAM MENINGKATKAN BRAND AWARENESS FUJISHOPID BALI - Putu Jista Prajna Dana Devi; Relin D.E; Ida Ayu Tary Puspa (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2025)
Community empowerment after the Covid-19 pandemic has opened up 760 thousand people have opened new businesses since the Covid-19 pandemic, and 40% of business actors after the Covid-19 pandemic use social media marketing communication to reach a more massive audience. The use of social media aims to build brand awareness for a brand because social media has many business features that help marketing activities.This research aims to find out how Instagram social media as a marketing medium increases Fujishopid Bali brand awareness. This research uses qualitative research methods presented in narrative form. The results of this research show that: (1) The forms of marketing carried out by Fujishopid Bali are online and offline marketing, namely advertising on Instagram social media, public relations, personal selling, sales promotions and interactive marketing; (2) The strategy of using Instagram social media as a marketing medium is used to disseminate product information offered by Fujishopid Bali which is uploaded in the form of photos or short videos via the Instagram story feature, Instagram feeds and Instagram reels to increase interaction which can increase brand awareness of Fujishopid Bali in the minds of the public; (3) The strategy for establishing Fujishopid Bali's brand image is carried out by establishing brand equity, brand positioning, sustainable brand awareness and becoming the brand preference for Fujifilm sales stores in Bali so that this brand preference indicates an increase in Fujishopid Bali brand awareness in the minds of the public.